Essential Oil Profile Diversity in Cardamom Accessions From Southern India - Ashokkumar, Kaliyaperumal; Vellaikumar, Sampathrajan; Murugan, Muthusamy; Dhanya, M. K.; Ariharasutharsan, Gunasekaran; Aiswarya, Shaji; Akilan, Manoharan; Warkentin, Thomas D.; Karthikeyan, Adhimoolam (Frontiers in Sustainable Food Systems, 2021)
The essential oil of cardamom capsules is a high-value ingredient in foods, beverages, perfumery, and traditional medicines. It is responsible for the characteristic aroma of cardamom. The present study aimed to evaluate essential oil yield and chemical constituents of 22 diverse accessions of cardamom. A total of 20 g of the cured capsules were hydrodistilled in a Clevenger apparatus for 3 h in three replications. The amount of essential oil yield ranged from 4.5 to 9.5%, indicating a substantial variation in this feature among the accessions. The GC/MS analysis results discovered 24 constituents that constituted 98.1–100% of total essential oil. The main fractions were found to be oxygenated monoterpenes (40.7–66.7%), monoterpene hydrocarbons (23.1–58.6%), and sesquiterpenes (0.1–2.0%). Among the monoterpenoids, the predominant constituents were α-terpinyl acetate (29.9–61.3%) followed by 1,8-cineole (15.2–49.4%), α-terpineol (0.83–13.2%), β-linalool (0.44–11.0%), and sabinene (1.9–4.9%). Two sesquiterpene constituents, cardinen and nerolidol and p-cresol (a phenol derivative) were also identified. The compositional data were subjected to euclidean-distance-based similarity analysis, which showed two major clusters. The major constituents of cardamom essential oil (CEO) are 1,8-cineole, α-terpinyl acetate, sabinene, and β-linalool that can be used in food, aroma, and pharmaceutical applications.